In the Hot Seat: Behavioral Change and Old-Growth Trees Underpin an Australian Songbird’s Response to Extreme Heat - Sharpe, Lynda L.; Prober, Suzanne M.; Gardner, Janet L. (Frontiers in Ecology and Evolution, 2022)
Anthropogenic climate change is increasing the frequency and intensity of heat waves, thereby threatening biodiversity, particularly in hot, arid regions. Although wild endotherms can use behavioural thermoregulation to resist heat, it remains unclear to what degree behaviour can buffer organisms from unprecedented temperatures. Thermoregulatory behaviours that are efficacious in moderate heat (facilitating dry heat loss) become maladaptive once environmental temperatures exceed body temperature. Additionally, behavioural thermoregulation carries costs (which may become untenable with greater heat exposure) and may be dependent upon specific microhabitats. Only by understanding how these three elements (responses, costs and habitat) intersect, can we hope to predict how heatwaves will impact wild endotherms. We quantified the thermoregulatory behaviours and microhabitat use of a small passerine, the Jacky Winter (Microeca fascinans), in the mallee woodland of SE Australia. This population has experienced a doubling in days ≥42 C over the last 25 years. The birds’ broad repertoire of behavioural responses to heat was nuanced and attuned to environmental conditions. However, it was associated with reduced foraging effort and increased foraging costs, accounting for the loss of body condition that occurs at high temperatures. By measuring microsite surface temperatures – which varied by up to 35 C at air temperatures >44 C - we found that leaf-litter coverage and tree size were positively associated with thermal buffering. Large mallee eucalypts were critical to the birds’ response to very high temperatures, providing the highest perches (facilitating “forced” convective cooling), the coolest tree-base temperatures and the greatest prevalence of tree-base crevices or hollows (used as refuges at air temperatures >38 C). Tree-base hollows, found only in large mallees, were cooler than all other microsites, averaging 2 C cooler than air temperature. Despite the plasticity of the birds’ response to heat, 29% of our habituated study population died when air temperatures reached a record-breaking 49 C.